Studi Fenomenologi Pengalaman Kecemasan dengan Pendekatan Paliatif pada Pasien dengan Ulkus Diabetikum. - Muhammad Anis Taslim; Sri Puguh Kristiyawati (NHM PRESS, 2023)
Introduction: Diabetic foot ulcers one of the complications that often occur in patients with Diabetes Mellitus (DM) due to uncontrolled glucose in the blood properly. Diabetes Mellitus experienced by patients not only has an impact on physical changes, but also changes in psychological responses to illness. Anxiety is one of the psychological responses experienced by patients with DFU due to changes in health, loss of function, and incomplete conditions that occur in the body such as injuries and amputations. Method: This research design is qualitative with a phenomenological study approach. This study aims to explore and describe the experience of anxiety in diabetic ulcer patients through in-depth interpretation of the subjectivity of the participants, so that understanding, meaning and phenomena are obtained. Participants who have obtained as many as 8 participants. The analysis used by using colaizzi data analysis. Results: The themes found in this study are 3 themes which include: causes of anxiety, effects of anxiety, and expectations. The hope that all participants wanted was the hope of healing from diabetic foot ulcers.